Factors influencing decision on job application: A study of graduate’s business school perspective - Mansor, Mohd Fitri; Halim, Nabilah Huda; Mohd Yusof, Bibi Noraini; Abu, Noor Hidayah (INSInet Publications, 2014)
Manpower is the greatest assets in any business field.Recruitment and selection process are important for new and established businesses.Successful organizations will be those that are able to attract and retain highly skilled employees in achieving the mission, vision and objectives of the organizations.Objective: Therefore, this study mainly investigates the factors influencing decision on job application in the perspective of graduate’s business school.The objectives of the study are to determine the relationships between online recruitment and website characteristics toward graduate’s decision on job application. Results: This study used the quantitative method by distributing questionnaires to 150 business school graduates in one of the public university in Malaysia.The hypotheses have been tested by using a multiple regression analysis.The results of the study revealed that, both online recruitment and website characteristics factors supported and influenced the graduate’s business school towards their job application Conclusion: The findings and framework of this study will be useful to students and practioners on how online recruitment and website characteristics influence the graduate’s decision to apply the job application. The study also serves a guideline to the organization to strategize the recruitment and selection process in their organization.